Anti-Obesity and Lipid Lowering Activity of Bauhiniastatin-1 is Mediated Through PPAR-γ/AMPK Expressions in Diet-Induced Obese Rat Model - Karunakaran, Reddy Sankaran; Lokanatha, Oruganti; Muni Swamy, Ganjayi; Venkataramaiah, Chintha; Muni Kesavulu, Muppuru; Appa Rao, Chippada; Badri, Kameswara Rao; Balaji, Meriga (Frontiers in Pharmacology, 2021)
Objective: To evaluate the therapeutic efficacy and underlying molecular mechanisms of Bauhiniastatin-1 (BSTN1) to alleviate adiposity in diet-induced obese rodent model and in 3T3-L1 cells. Methods: BSTN1 was purified and confirmed through HPLC. In-vitro experiments such as MTT assay, Oil Red-O (ORO) stain, cellular lipid content, glycerol release and RT-PCR analysis were performed in 3T3-L1 cells in the presence and absence of BSTN1. In animal experiments, rats were divided into Group-I: normal pellet diet-fed, Group-II: HFD-fed, Groups-III, IV & V: HFD-fed BSTN1 (1.25, 2.5 and 5 mg/kg.b.wt./day/rat)-treated and Group-VI: HFD-fed Orlistat-treated. The rats were fed either normal diet or high fat diet (HFD) for 18 weeks and water ad-libitum. BSTN1 was orally administered from 13th week onwards to the selected HFD-fed groups. Body composition parameters, biochemical assays, histopathology examination and western blot analysis were performed to identify the predicted targets related to obesity. Molecular docking studies threw light on the binding interactions of BSTN1 against PPAR-γ, FAS and AMPK. Results: BSTN1 at 20 μM significantly (p < 0.001) inhibited adipocyte differentiation and lipid accumulation in 3T3-L1 cells. A conspicuous down-regulation in the mRNA expression levels of PPAR-γ, FAS and SREBP1 was observed but AMPK expression remained unchanged in BSTN1 treated 3T3-L1 cells. A substantial decrease in body weight gain, fat percent, total body fat, serum & liver lipid profile (except HDL), glucose, insulin and insulin resistance in BSTN1 treated rats was noticed in a dose dependent manner. In BSTN1 (5 mg/kg.b.wt.)-treated groups significantly (p < 0.01) elevated plasma adiponectin level but reduced leptin level as well as fall in serum AST and ALT were noticed. Further, the disturbed structural integrity and architecture of adipose & hepatic tissues due to HFD feeding were considerably recovered with BSTN1 treatment. Down-regulation in the protein expression level of PPAR-γ and activation of AMPK through phosphorylation was observed in BSTN1 treated rats than the untreated. Molecular docking studies revealed strong binding interactions of BSTN1 against PPAR-γ and AMPK and thus supported the experimental results. Conclusions: Taken together, the results suggest that BSTN1 could be a promising pharmacological molecule in the treatment of obesity and dyslipidemia.